2017
DOI: 10.1515/enr-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Th e eff ects of Nigella Sativa extract on renal tissue oxidative damage during neonatal and juvenile growth in propylthiouracil-induced hypothyroid rats

Abstract: Objective. We investigated the eff ects of hydroalcoholic extract of Nigella sativa (NS) on renal tissue oxidative damage associated with propylthiouracil (PTU)-induced hypothyroidism during neonatal and juvenile growth in rats.Methods. Pregnant rats were divided into fi ve groups designated as: 1) control; 2) propylthiouracil (PTU); 3) PTU-NS100; 4) PTU-NS200, and 5) PTU-NS400. All mothers except the control group received 0.005% PTU in their drinking water during lactation. Besides PTU, mothers in groups 3-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
(38 reference statements)
3
16
0
Order By: Relevance
“…On the other hand, the current study demonstrated a significant upregulation of catalase gene expression in the kidney of the hypothyroid+TQ group, which was in an agreement with Khan et al [31]. Mohebbati et al [14] also reported an increase in CAT and SOD activity in renal tissues following administration of 200 and 400 mg/kg of N. sativa extract compared to the PTU group.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the current study demonstrated a significant upregulation of catalase gene expression in the kidney of the hypothyroid+TQ group, which was in an agreement with Khan et al [31]. Mohebbati et al [14] also reported an increase in CAT and SOD activity in renal tissues following administration of 200 and 400 mg/kg of N. sativa extract compared to the PTU group.…”
supporting
confidence: 92%
“…In addition, NS and TQ were recently reported to have the potential to prevent renal tissue damage and fibrosis in lipopolysaccharide-(LPS-) treated rats through its antioxidant and anti-inflammatory effects [12,13]. It was reported that the hydroalcoholic extract of NS could protect the renal tissue against oxidative stress associated with neonatal and juvenile hypothyroidism in rats [14] None of the available studies neither investigated the effect of the TQ in specific, the bioactive constituent of NS, on the structure of the renal tubules of hypothyroid animal model nor tried to explore the mechanism behind this effect. Therefore, the aim of this study was to evaluate the possible protective effects induced by TQ on the histological and biochemical changes that occur in the renal cortex of hypothyroid rats and elucidate the mechanism by which these effects were induced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormones are necessary for carrying out cellular functions in the body. It is also known that these hormones act on oxidative and antioxidative states (Joshi et al., 2018; Mohebbati et al, 2017). OS, which emerged with the change in oxidant and antioxidant balance in favor of oxidants, has an important role in the etiology of many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…ROS formation as a result of the changes in thyroid hormones has been reported to be conflicting in both HT and hyperthyroidism in many studies. (Aslan et al., 2011; Cano‐Europa et al., 2010; Harper & Seifert, 2008; Mohebbati et al., 2017; Ortiz‐ButrÓn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%